Between Past and Future - 1/7
Continuation of the debate between the audience, the journalists and the members of the media panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference that was held at CEU in March 1999. The members of the panel are R. W. Apple Jr. (Chief Correspondent, “New York Times”), Barrie Dunsmore (Former Senior Correspondent, ABC News), James Carney (Political Correspondent, “Time Magazine”), Flora Lewis (Senior Columnist, “New York Times” Syndicate), Ambassador Richard Holbrooke (U.S. Special Envoy to Yugoslavia) and György Bolgár (Journalist and Broadcaster, Hungarian Radio). The moderator of the discussions is Kati Marton. The next panel entitled “Meanings of 1989 and the Present Significance of the Past” is the academic panel, chaired by Vladimir Tismăneanu (Professor at Maryland University) who is also an organizer and speaker of the conference. The panel is composed of Jacques Rupnik (Institute of Political Studies, Paris), Tamás Gáspár Miklós (Georgetown University), Karol Soltan (University of Maryland), Daniel Chirot (University of Washington) and Sorin Antohi (Academic Pro-Rector at CEU). The tape contains Jacques Rupnik’s speech.